ZAWARTOŚĆ INFORMACYJNA NABYWANIA AKCJI WłASNYCH - Będowska-Sojka, Barbara (Wydział Prawa i Administracji UAM, 2003)
The literature on the subject points at the signalling hypothesis as one of the reasons for shares repurchase. This paper describes the market reaction to announcement of buy-back. It has been found that a statistically relevant, abnormal rate of return occurs in 5, 7, 9, 11, 21 and 41 day time frame around the day of announcement. Based on the sample group of 42 announcements of share repurchase it is highly probable that the reaction of the market to buy- -back would be strong and positive in the short term. As compared against other markets, abnormal rates of return on the Polish market are relatively high. In order to verify the signalling hypothesis, a regression analysis has been adopted together with the explanatory variables recommended in the literature. According to the hypothesis, there is a stronger market reaction to the announcement of share repurchase published by smaller companies which are characterized by greater information asymmetry. A characteristic feature in this case is also a positive reaction of the market to the repurchase of a greater share stake. The signalling hypothesis also argues that companies announce share buy-back after the value of their shares deteriorated. The conducted regression analysis has not corroborated the fluctuation of the variable describing the share risk, which proves to the contrary of the signalling hypothesis. Here, the cumulated abnormal return decreases with the increase in the share risk. Such reaction of the market may be ascribed to unwillingness o f investors to buy high-risk shares. Unfortunately, a relatively small sample and a short research period prevent a detailed analysis of the changes in the company profits. Further research on the subject will allow further verification of the signalling hypothesis on the Polish capital market. However even now it can be argued with a certain degree of probability that, similarly to foreign markets, by means of share repurchase the companies signal undervaluation and that the Polish market is not very different from the mature capital markets.
THE INFORMATION CONTENT OF SHARE REPURCHASE